Amenities as a Brand Strategy and Customer Delight - Rayane Silva , Míriam (2021)
The personal care amenities made available to guests by lodging establishments, present themselves as potential elements to generate added value, enchant, delight and retain guests and to give greater visibility to their brands. Therefore, this work analyzes, in two stages, the personal care amenities offered by the hotels located on Via Costeira in the city of Natal, Rio Grande do Norte, Brazil. First, we sought to identify which products are offered and their differentiating attributes. Then, a quality assessment was carried out based on the perception of specialists, and a comparison between the products used by the hotels surveyed, in order to discuss the possible contributions, they provide to their brands. The study adopted a qualitative, descriptive-exploratory methodological approach, and used the “blind test” technique for data collection, and content analysis for data handling. In view of the results obtained, it is concluded that the amenities offered by most Via Costeira hotels do not present significant differentials, revealing the need to improve their quality and use as a brand strategy and customers delight by the hotels surveyed.